In Search of a Liberatory Appraisal for Palestinian Archives - Sandock, Andrew (Archivaria, 2025)
⁠⁠⁠⁠⁠⁠⁠In November 2023, the Central Archives of Gaza was bombed during Israel’s ongoing incursion in the strip, reducing 150 years of the cultural record to ash. This attack is but one moment in the long history of archival theft and destruction in Palestine, the culmination of a sphere of colonial epistemicide. Palestinian ways of knowing face a constant threat of annihilation, and Palestinian archives are built under the looming peril of physical destruction. Palestinian archives struggle to appraise for the future and engage instead in massified forms of appraisal and digitization in efforts to preserve everything they can in the face of these threats. Taking stock of some current prominent instances of archival projects in Palestine, this article thinks through some current approaches to appraisal, wondering if they apply here and whether they can be expanded to account for the particularities of this environment. It then attempts to reimagine what a liberatory appraisal might look like, thinking about the Palestinian archive as a counter to epistemic violence and exploring the processes through which appraisal methods and categories might be gleaned by anticipating liberated futures.